Modeling the effect of postgraduate courses on soft skills: a practical approach - Pinos Ullauri, Luis Alberto; Lebis, Alexis; Karami, Abir; Vermeulen, Mathieu; Fleury, Anthony; Van Den Noortgate, Wim (Frontiers in Psychology, 2024)
Over the last decade, Higher Education has focused more of its attention towards soft skills compared to traditional technical skills. Nevertheless, there are not many studies concerning the relation between the courses followed within an academic program and the development of soft skills. This work presents a practical approach to model the effects of courses on soft skills proficiency. The models are trained with real data from students of the 2021, 2022 and 2023 cohorts from the general engineering program in a French Higher Education institution. The results show that attending a postgraduate course in average increases the odds of being more proficient in terms of soft skills. Nonetheless, there is considerable variability in the individual effect of courses, which suggest there can be huge differences between courses. Moreover, the data also suggest great dispersion in the students' initial soft skill proficiency.